Governance of Information and Communication Technology Development at Gorontalo State University - Usulu, Wahidin; Kamuli, Sukarman; Aneta, Yanti; Badjuka, Alexander H. (Abdurrauf Science and Society, 2025)
The governance of information and communication technology (ICT) has become a strategic necessity for higher education institutions to ensure effective academic services and sustainable digital transformation. This study aims to analyze the ICT governance system at the Academic Service Unit for ICT (UPA TIK) of Gorontalo State University. A qualitative case study design was employed. Data were collected through in-depth interviews, document analysis, and direct observation, and analyzed using the Miles and Huberman interactive model. Triangulation was applied to ensure data credibility and validity. The results reveal five governance dimensions: (1) strategic alignment, (2) organizational structure, (3) managerial competence, (4) resource allocation, and (5) institutional culture. While ICT development has been integrated into the university’s strategic plan and supported by adequate infrastructure, weaknesses remain in managerial competence, fragmented decision-making, and limited funding. Institutional culture shows positive digital acceptance but is still constrained by resistance to change. This study concludes that effective ICT governance requires clear organizational structures, competent leadership, and stakeholder participation. The novelty of this research lies in proposing a contextualized governance model for Indonesian higher education, balancing global ICT frameworks with local organizational and cultural dynamics. These findings contribute theoretically to the discourse on digital governance and provide practical recommendations for policymakers in strengthening digital transformation in higher education.